Mediação bibliotecária no contexto universitário para a busca e recuperação de evidências científicas em saúde: desafios e reverberações - Gesner Francisco Xavier Junior (2022)
Introduction: access to the main scientific evidence available in the literature is a pressing demand of students, professors/researchers and professionals working in the health area. However, one of the great current challenges in the university context, in general, and in scientific research, in particular, which is not limited to the health area, but is notable in it, is precisely to seek and retrieve relevant and quality information. For this reason, in university libraries inserted in the health context, the search for studies in databases is regularly carried out by librarians in cooperation with users. Although library support is, in particular, a service whose purpose is the search/retrieval of studies, it is believed that the results of mediation have implications beyond the sensitivity and scope of the information/evidence located. Objective: to analyze, from the point of view of reference librarians inserted in Higher Education Institutions (HEI) in Minas Gerais (MG) that offer undergraduate courses in the area of health and based on the theoretical contributions of information mediation, the characteristics of the support service for the search for studies in databases, their challenges and how the sociopolitical reverberations of this work are presented in the institutional scope, in the scientific field and in health practices. Methodology: The HEIs located in the state of MG that offer undergraduate courses in Nursing, Pharmacy, Medicine and Dentistry are the research universe, targeting reference librarians and professors/researchers who work in these institutions. Before data collection, an exploratory phase was carried out in order to map and characterize the research universe. At this stage, the following data were detailed: distribution of Nursing, Pharmacy, Medicine and Dentistry courses by region of the state of MG, academic organization and administrative structure of the HEIs that offer these courses, in addition to the concept of each course with the Ministry of Education/National Institute of Educational Studies and Research Anísio Teixeira. Considering the research objectives, data collection was carried out in two stages: in the first, an electronic questionnaire (survey) was sent to the libraries of the 138 institutions that make up the research universe, with reference librarians as the target audience. From this universe, 71 librarians responded to the questionnaire. The results of this stage were grouped into four topics: profile and academic-professional training of librarians; the reference service and support for the search for studies in databases; librarians' self-perception regarding familiarity and use of research resources; strategies adopted to maintain search skills. In the second stage of data collection, semi-structured interviews were carried out with librarians and professors/researchers. The sample consisted of 10 librarians, one from each region of the state of MG, and four professors/researchers, with experience working with at least one of the courses that make up the universe of research interest (Nursing, Pharmacy, Medicine and Dentistry). In order to analyze the responses obtained in the interviews, the technique of content analysis was used, using Bardin's notes as a reference. In view of the theoretical framework and the research objectives, four analytical categories were established: the university library in the context of health; the reference librarian and the study search support service; librarian mediation to search for studies in databases in the health area; and sociopolitical reverberations of library mediation. Results: the singularities of the work process in university libraries are determined not only by the idiosyncrasies of health personnel and by the characteristics of the practical, theoretical and methodological field, but, above all, by the fact that human health (physical and mental) is the object of study and practice in the area. Given the complexity of the librarian mediation process for the search for studies, professionals are required to be concerned with the dialectic of this relationship and to develop a critical and reflective concern that goes beyond the eminently technical aspects of mediation. In addition to the assertiveness of the studies retrieved in the face of the problem presented, the librarian's performance has reverberations in the quality of institutional scientific production, which, in turn, will impact the conformation of the scientific field and, ultimately, health care practices. Directly or indirectly, library support has the potential to impact the entire health ecosystem. Therefore, on the part of librarians, mediation in the university context for the search for scientific evidence must be read and understood beyond a utilitarian perspective, simplifying it into just one service that ends with the delivery of results. Otherwise, the reference librarian would be seen more as an intermediary than a mediator. However, the librarian action, translated from their knowledge, attitudes and skills, is loaded with intentionality and built from the dialectical relationship that is established with the user and that is permeated by the competence in information and the search behavior. Conclusion: despite the challenges related to librarian training in Brazil to work in specialized contexts and the difficulty of professionals to develop skills and abilities that are desirable and/or required for health work, such elements do not constitute an obstacle to the practice professional. On the contrary, the research data reveal that professionals see in the gaps in the training process a window of opportunity for the apprehension of new knowledge. In any case, in view of the power of librarianship in the field of health and the social responsibility derived from it, it is up to professionals, as a class, to assume an effective role of protagonism in supporting scientific research and in the academic-professional training of the staff of the health. In spite of the challenges related to the macrosocial aspects of higher education in Brazil, the working conditions of librarians within the HEIs and also the stigmatized profile historically built around the profession, in practical terms, both the vitality and the relevance of libraries university students in health are related to the actions of reference librarians. Therefore, criticality must be inherent to professional actions and choices, given its implications for the health care of the population.